A GENDERED TAXONOMY ON HOUSING PRECARITY: CHALLENGES FROM LISBON METROPOLITAN AREA DURING THE COVID-19 PANDEMIC - Pestana Lages, Joana; Jorge, Sílvia (Sociedade e Território, 2023)
‘How to stay home?’ is a question that many posed when the COVID-19 pandemic forced us to stay indoors. Housing precariousness is still a problem for circa sixty thousand families in Portugal, to whom escaping poverty, and several types of discrimination is still hard. This paper is based on an action-research project focused on housing precariousness, aiming to build a taxonomy on the different experiences lived by women, under the neoliberal context of the Global North. Starting from 10 in-depth interviews, this paper makes investigates housing precarity from a gendered perspective, identifying the main inequalities before and during the pandemic, as well as the priorities proposed for/from women. The relation between housing and gender is questioned from the way we organize ourselves: socially and spatially. Understanding this relation can be a catalyst to better responses and effective public policies, and more effectively end precarity.